2012
DOI: 10.1128/jcm.06701-11
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pathogen and Host Factors Related to Clinical Outcomes in Patients with Hospital-Acquired Pneumonia Due to Methicillin-Resistant Staphylococcus aureus

Abstract: dMethicillin-resistant Staphylococcus aureus (MRSA) is a major cause of nosocomial pneumonia. To characterize pathogen-derived and host-related factors in intensive care unit (ICU) patients with MRSA pneumonia, we evaluated the Improving Medicine through Pathway Assessment of Critical Therapy in Hospital-Acquired Pneumonia (IMPACT-HAP) database. We performed multivariate regression analyses of 28-day mortality and clinical response using univariate analysis variables at a P level of <0.25. In isolates from 251… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 28 publications
4
41
1
1
Order By: Relevance
“…In addition, outcomes observed here may be related to host characteristics rather than bacterial virulence. Observational studies of invasive MRSA infections in the United States have reported that the underlying disease severity of the infected individual, rather than the SCCmec type, was the main risk factor associated with mortality [17,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, outcomes observed here may be related to host characteristics rather than bacterial virulence. Observational studies of invasive MRSA infections in the United States have reported that the underlying disease severity of the infected individual, rather than the SCCmec type, was the main risk factor associated with mortality [17,32].…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating the molecular epidemiology of MRSA in patients with CF in the United States have reported approximately two-thirds of MRSA strains were SCCmec II [13][14][15]. In non-CF MRSA disease, outcomes may be different based on SCCmec status [16,17]. However, outcomes associated with different SCCmec types have not been addressed in CF patients with chronic lung infections, and SCCmec status is not currently used in clinical care.…”
Section: Introductionmentioning
confidence: 99%
“…35 Furthermore, we were unable to molecularly classify the MRSA isolates; molecular differences in MRSA strains have been shown to affect clinical results. [14][15][16] Susceptibility data and trough data were not available, and therefore it is not known if subjects reached therapeutic levels of the treatment agent.…”
Section: Resultsmentioning
confidence: 99%
“…For example, age, underlying comorbidities, severity of illness, multiple lobe involvement, and need for intensive care unit (ICU) admission have been associated with poor clinical outcomes. [9][10][11]13,14 There are multiple differences among MRSA strains on a molecular level, including staphylococcal cassette chromosome mec (SCCmec) type, presence of the toxin Panton-Valentine leukocidin, and minimum inhibitory concentration, which can affect clinical outcomes. [14][15][16] MRSA pneumonia is a complex disease associated with significant morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…MRSA isolates present a staphylococcal cassette chromosome mec (SCCmec), and types II, III and IV are the most frequent [2,3,4]. Epidemiological studies conducted in recent years have shown that SCCmec IV isolates, mainly related to USA300 and European clones, are found in about 80% of MRSA isolates collected from community and hospital settings in Europe [2].…”
mentioning
confidence: 99%